The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1111/j.1438-8677.2012.00654.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated CO2 concentration and water deficit on fructan metabolism in Viguiera discolor Baker

Abstract: Elevated [CO2 ] is suggested to mitigate the negative effects of water stress in plants; however responses vary among species. Fructans are recognised as protective compounds against drought and other stresses, as well as having a role as reserve carbohydrates. We analysed the combined effects of elevated [CO2 ] and water deficit on fructan metabolism in the Cerrado species Viguiera discolor Baker. Plants were cultivated for 18 days in open-top chambers (OTC) under ambient (∼380 ppm), and high (∼760 ppm) [CO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 53 publications
(85 reference statements)
2
15
1
2
Order By: Relevance
“…As medições confirmam que a proporção de CO 2 , dentre os gases atmosféricos, aumentou globalmente de 280 ppm na era pré-industrial para 379 ppm em 2005 e, atualmente, já está em média 400 ppm (NOAA 2017). Este fato, associado ao potencial que as plantas possuem de assimilar carbono atmosférico por meio da fotossíntese e da produção de compostos de carbono, faz com que estudos sobre o crescimento, desenvolvimento e metabolismo de plantas sob elevadas concentrações de CO 2 recebam ampla atenção (Long & Bernarcchi 2003, Braga et al 2006, Kretzschmar et al 2009, Oliveira et al 2013.…”
Section: Introductionunclassified
“…As medições confirmam que a proporção de CO 2 , dentre os gases atmosféricos, aumentou globalmente de 280 ppm na era pré-industrial para 379 ppm em 2005 e, atualmente, já está em média 400 ppm (NOAA 2017). Este fato, associado ao potencial que as plantas possuem de assimilar carbono atmosférico por meio da fotossíntese e da produção de compostos de carbono, faz com que estudos sobre o crescimento, desenvolvimento e metabolismo de plantas sob elevadas concentrações de CO 2 recebam ampla atenção (Long & Bernarcchi 2003, Braga et al 2006, Kretzschmar et al 2009, Oliveira et al 2013.…”
Section: Introductionunclassified
“…Our data corroborate the results obtained by Gratani et al (2008), who showed that bamboo species have a high capacity to adjust their photosynthetic rates under severe environmental conditions. Current knowledge indicates that most tropical plants grow best under CO 2 enrichment (Aidar et al 2002;Souza et al 2008;Krorner 2009;Oliveira et al 2010Oliveira et al , 2012.…”
Section: Resultsmentioning
confidence: 99%
“…In general, water content of the sampled underground organs was lower than that reported for other species. For example, rhizophores of irrigated C. obovata plants had 85 % water content (Garcia et al 2011), while the tuberous roots of irrigated A. discolor had 80 % (Oliveira et al 2013). Dimorphic thickened roots of field-grown I. terminalis plants had 61-85 %, with the highest values being during the rainy season (Almeida et al 2017).…”
Section: Water Contentmentioning
confidence: 99%